ENGLISH INSTRUCTIONAL MATERIALS FOR THE INTEGRATED ISLAMIC ELEMENTARY SCHOOL (SDIT) - Melati Sri Utami; Endang Fauziati; Dewi Rochsatiningsih (Siliwangi University, 2019)
The global trend to include English program in the early years of primary education in recent years has given ascend to the need for experienced teachers who was teaching English to young learners. There are kind of instructional materials for teaching English to the young learners. However, not all of instructional materials can be used effectively and appropriately in the classroom especially in an integrated Islamic school which is adopted and combined both government curriculum and integrated Islamic curriculum. Therefore, this research aims in investigating kind of instructional materials that generally used by the English teacher and the impacts of using instructional materials toward the learning environment. Further, the researcher also described the challenges of English teachers in adopting the instructional materials at integrated Islamic elementary school. To reach the aims, a descriptive qualitative study design is conducted towards the participants: seven English teachers from different integrated Islamic elementary schools in Central Java. The research employed questionnaire and interview to obtain the deeper data. The findings of the research are expected to provide an overview for English teacher in choosing the appropriate instructional materials with any considerations since they can motivate the young learners in learning English as a foreign language especially at the integrated Islamic elementary school.